MENINGKATKAN KOMPETENSI PEDAGOGIK GURU NON KEPENDIDIKAN - Pardede, Lukman (Jurnal Darma Agung; Vol 27 No 2 (2019): AGUSTUS 2019, 2019)
This study aims at improving the pedagogical competence of non-educational background teachers in compiling learning plans through the academic supervision of principals.This research was began on March 2019 and ended on May 2019. The subject of this research is 6 teachers. This research was conducted in SMA N 17 Medan in which themethod used is Classroom Action Research (CAR) referring to F. X. Sudarsono who said that one activity consists of 4 cycles; they are:planning, acting, observing and reflecting. This research covered in two cycles. Data analysis was done by using qualitative method taken by observing during the implementation by using field note, meanwhile the quantitative data was taken by comparing the average score of pre-test and post-test. After pre-cycles, cycle I and cycle II, it canbe concluded that there is significant improvement from cycle I to cycle II. The dimension of the formulation of learning objective indicators for the initial 30% increased to be 65% in cycle I and increased again significantly to 90%. The dimensions of the determination of teaching materials and learning materials were initially 40% increased to 70% in the first cycle and increased again to 90% in the second cycle. The strategy selection dimension and learning method from 30% in the initial data to 60% in the first cycle, increased again to 80% in the second cycle. The dimensions of the method selection and learning tools depict the initial data 35%, but in the first cycle increased to 65% and increased significantly again in the first cycle to 85%. In the learning evaluation planning dimension, the initial data description is 30%, the first cycle becomes 65%, increasing again to 80% in cycle II. The implicationn of this research is that academic supervision activities are very well done to foster teachers in improving their competence. It is recommended that this activity be carried out in a planned and sustainable manner, to measure the teacher's ability in implementingthe learning plan prepared.